A research on the pollution parameters of buttermilk - Kirdar, Seval Sevgi; GENÇ, Didem Gamze (Indian Journal of Dairy Science, 2020)
Buttermilk and butter-washing water obtained during butter production in some production facilities in Turkey are released directly into the sewer system without being evaluated or tested for their components. These byproducts can cause environmental pollution from their nutrient composition and concentrations. Buttermilk is an industrial waste that has a high organic load because it contains all the components of milk solids. The aim of this study was to determine the waste composition and chemical oxygen demand (COD) of buttermilk, one of the main pollutants from the dairy industry because of its levels of organic matter. Nine buttermilk samples obtained from three different butter-production plants in Burdur and Isparta, Turkey, were sent to the laboratory under cold chain (+ 4°C). The average values of fat, protein, lactose, solids, and ash of the buttermilk samples were 1.38 ± 0.37, 0.77 ± 0.123, 5.12 ± 0.11, 7.92 ± 0.36, and 0.676 ± 0.027 mg/L, respectively, at pH 4.70 ± 0.05. COD was 94866.67 ± 10091.82 mg/L.